2017
DOI: 10.1097/lgt.0000000000000282
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Sexual Distress in Women With Erosive Vulvovaginal Lichen Planus

Abstract: Sixty-nine percent of women with EVLP reported sexual distress. Women with EVLP reported lesser quality of life than those with lichen sclerosus. Quality of life, anxiety and depression, sexual distress, and sexual function were all related in these participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 18 publications
1
36
0
Order By: Relevance
“…A US study documented high rates of sexual dysfunction in vulvar clinic patients . Another study found that high levels of sexual distress were recorded by 69% of women with LP and 63% of women with lichen sclerosus. In our study, we asked women to consider whether they had active or inactive sexual life, and we found that 64% of all patients declared to be sexually inactive.…”
Section: Discussionmentioning
confidence: 99%
“…A US study documented high rates of sexual dysfunction in vulvar clinic patients . Another study found that high levels of sexual distress were recorded by 69% of women with LP and 63% of women with lichen sclerosus. In our study, we asked women to consider whether they had active or inactive sexual life, and we found that 64% of all patients declared to be sexually inactive.…”
Section: Discussionmentioning
confidence: 99%
“…In our case, although remission of symptoms such as pain and pruritus had occurred, sexual dysfunction was a constant, showing little improvement. Cheng and colleagues [16] demonstrated that 63% of the patients with LS had sexual dysfunction. Quality of life is also extremely affected in this disease.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, sexual dysfunction has been the chief objective for some investigators. 6,10 However, in our experience a relevant number of patients affected with vulvar inflammatory disorders do not have sexual activity, not only because of disease-related pain or distress. 13 Thus, in many cases tools specifically addressing sexual behaviour may be inadequate for a more comprehensive assessment of the suffering caused by vulvar inflammatory conditions.…”
Section: Introductionmentioning
confidence: 95%
“…The available literature has mainly focused the burden of vulvar LS [4][5][6][7][8][9] and, to a lesser extent, LP. 10 From these studies, it emerged that vulvar LS and LP can negatively affect patients' daily lives and significantly impair their physical and social activities, mental health and intimate relationships. Other vulvar inflammatory conditions have been studied marginally from this point of view.…”
Section: Introductionmentioning
confidence: 99%